Culture over Structure: The Heritage of Lifestyle Research in the 1970s in Hungary and Poland - Filipkowski , Piotr; Gárdos, Judit; Kovács, Éva; Szabari, Vera (Stan Rzeczy, 2017)
In our article we will present two Eastern European examples of how sociological research on everyday life in the 1970s has been influenced by political and cultural circumstances and particular scientific traditions. From the early 1970s, sociology flourished in some countries of the Eastern Bloc, institutes were refounded, and research projects were heavily subsidised. Research into daily life – the so-called “socialist lifestyle” – was one of the main foci of sociological inquiry. Recently, similar data collections from two such projects were discovered in the archives of academies of sciences in Hungary (HAS) and Poland (PAS). In both cases, we can see that the researchers stand decisively on the side of “high” culture, while taking a normative view of “low” cultural consumption. Even though there was no direct cooperation or interdependence between Hungarian and Polish “lifestyle” researchers, we can observe similar structures of thinking about socialist society. Western influence, mostly implicitly, is also visible.